The Influence of Key Opinion Leaders on Generation Z Purchasing Decisions on Social Media - Erislan Erislan (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The Influence of Key Opinion Leaders on Generation Z Purchasing Decisions on Social Media. This study examines how Key Opinion Leaders influence purchasing decisions among Generation Z in Indonesia through credibility, content alignment, and interaction intensity on social media platforms. The research aims to identify the relative strength of these factors in shaping consumer purchase behavior in a digital marketing context. A quantitative explanatory design was employed, with data collected from 300 Generation Z respondents who actively use Instagram and TikTok. The data were analyzed using Structural Equation Modeling. The results show that credibility, content alignment, and interaction intensity all have a positive and significant effect on purchasing decisions, with credibility emerging as the most influential factor. These findings indicate that trustworthiness and expertise of influencers play a central role in digital persuasion, supported by relevant content and interactive engagement. The study concludes that effective influencer marketing strategies targeting Generation Z should emphasize credible opinion leaders, authentic content alignment, and meaningful interaction to enhance purchasing decisions.